Politics and fan communication in football stadia in Germany - a multimodal linguistic analysis of protest banners - Callies, M. (Soccer & Society, 2023)
Various forms of multimodal fan communication, e.g. choreographies, chants, and banners, have been understudied in linguistic research on the language and linguistics of football to date. In particular, banners have received almost no attention despite the fact that they are one of the most visible and attention-getting forms of direct fan communication in the stadium. Fan banners are often used to visually express protest through rather unconventional and creative linguistic forms of provocation. The massive commercialization and marketization of football has been subject to fundamental criticism that has caused conflicts and tensions in which defiant fan subcultures protest the unwanted modernization and sell-out of the game. In this paper I apply a netnographic approach and analyse the linguistic-semiotic characteristics and (meta-)pragmatic functions of protest banners displayed in stadia across Germany in early 2020. The findings suggest that meaning-making through fan banners and the de-coding of that meaning necessitates an understanding of the interplay of materiality, colour, text, imagery and sometimes temporality.